Detection Rate of Intravascular Injections during Cervical Medial Branch Blocks: A Comparison of Digital Subtraction Angiography and Static Images from Conventional Fluoroscopy - Jeon, Young Hoon (Korean J Pain, 2015)
BACKGROUND: The most definitive diagnosis of neck pain caused by facet joints can be obtained through cervical medial branch blocks (CMBBs). However, intravascular injections need to be carefully monitored, as they can increase the risk of false-negative blocks when diagnosing cervical facet joint syndrome. In addition, intravascular injections can cause neurologic deficits such as spinal infarction or cerebral infarction. Digital subtraction angiography (DSA) is a radiological technique that can be used to clearly visualize the blood vessels from surrounding bones or dense soft tissues. The purpose of this study was to compare the rate of detection of intravascular injections during CMBBs using DSA and static images obtained through conventional fluoroscopy. METHODS: Seventy-two patients were included, and a total of 178 CMBBs were performed. The respective incidences of intravascular injections during CMBBs using DSA and static images from conventional fluoroscopy were measured. RESULTS: A total of 178 CMBBs were performed on 72 patients. All cases of intravascular injections evidenced by the static images were detected by the DSAs. The detection rate of intravascular injections was higher from DSA images than from static images (10.7% vs. 1.7%, P < 0.001). CONCLUSIONS: According to these findings, the use of DSA can improve the detection rate of intravascular injections during CMBBs. The use of DSA may therefore lead to an increase in the diagnostic and therapeutic value of CMBBs. In addition, it can decrease the incidence of potential side effects during CMBBs.